Description of Self Efficacy that Affects Other Variables in Employees in A Company - Puspita, Aghi Viona Semas (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2024)
Introduction/Main Objectives: Individuals if they have high self-efficacy will have a positive attitude, tend to focus on success and tend to focus on goals. This self-efficacy if owned by employees will make them always try to solve every problem at work besides that it can improve performance to the maximum in proportion to the skills possessed by these employees. Background Problems: Self-efficacy is often associated with employee performance, achievement, and so on. Efficacy plays a very important role in everyday life. Self-efficacy can support individuals to optimize their potential. Research Methods: This research uses a literature study approach. Literature study is bringing together references which include research conducted previously, then compiled to make a conclusion. Finding/Results: Based on previous studies, it is found that self-efficacy in employees in a company greatly affects the level of employee readiness, employee performance, and job satisfaction and work performance positively and significantly. Conclusion: The conclusion from the results of this study is the importance of self-efficacy when owned by an employee who works in a company.